Suppression of the transcription factor MSX1 gene delays bovine preimplantation embryo development in vitro - Tesfaye, D.; Regassa, A.; Rings, F.; Ghanem, N.; Phatsara, C.; Tholen, E.; Herwig, R.; Un, C.; Schellander, K.; Hoelker, M. (BIOSCIENTIFICA LTD, 2010)
This study was conducted to investigate the effect of suppressing transcription factor gene MSX1 on the development of in vitro produced bovine oocytes and embryos, and identify its potential target genes regulated by this gene. Injection of long double-stranded RNA (LdsRNA) and small interfering RNA (siRNA) at germinal vesicle stage oocyte reduced MSX1 mRNA expression by 73 and 37% respectively at metaphase II stage compared with non-injected controls. Similarly, injection of the same anti-sense oligomers at zygote stage reduced MSX1 mRNA expression by 52 and 33% at 8-cell stage compared with non-injected controls. Protein expression was also reduced in LdsRNA- and siRNA-injected groups compared with non-injected controls at both stages. Blastocysts rates were 33, 28, 20 and 18% in non-injected control, scrambled RNA (scRNA), LdsRNA- and siRNA-injected groups respectively. Cleavage rates were also significantly reduced in Smartpool siRNA (SpsiRNA)-injected group (53.76%) compared with scRNA-injected group (57.76%) and non-injected control group (61%). Large-scale gene expression analysis showed that 135 genes were differentially regulated in SpsiRNA-injected group compared with non-injected controls, of which 54 and 81 were down-and up-regulated respectively due to suppression of MSX1. Additionally, sequence homology mapping and gene enrichment analysis with known human pathway information identified several functional modules that were affected due to suppression of MSX1. In conclusion, suppression of MSX1 affects oocyte maturation, embryo cleavage rate and the expression of several genes, suggesting its potential role in the development of bovine preimplantation embryos. Reproduction (2010) 139 857-870
Keywords: DOUBLE-STRANDED-RNA; BONE MORPHOGENETIC PROTEIN-15; INCREASED OVULATION RATE; NEURAL CREST; FOLLICULAR OOCYTES; CDNA MICROARRAY; EARLY-PREGNANCY; GROWTH-FACTORS; MESSENGER-RNA; AURORA-A; Developmental Biology; Reproductive Biology